Partisipasi Peserta Didik pada Program Adiwiyata Melalui Kegiatan Pengelolaan Sampah di Sekolah - Yessy Retno Ardianti; Susy Amizera; Rahmi Susanti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This research aims to determine the form of implementation of participation and the level of student participation in waste management at school. The method used in this research is descriptive qualitative research which aims to describe and analyze student participation in waste management through the Adiwiyata program which has been implemented in schools. The results of research on the implementation of student participation in managing types of waste at Adiwiyata High School in Palembang City include the use of trash bins based on type, and waste management participation activities by students. The use of trash cans by students has been implemented, but there are still students who have not thrown rubbish into trash cans based on the type. Student participation activities in waste management based on type include composting, clean Fridays, collecting, sorting and recycling waste, as well as a healthy canteen. The level of student participation in organic waste management has a percentage of 64.8% in the active category, inorganic waste management has a percentage of 71.3% in the active category, and B3 waste management has a percentage of 56.3% in the quite active category at Adiwiyata High School in Palembang City.